On the Role of Skorinian Editions in the Codification of the Byelorussian Church Slavic Language - Павловец, Д. Д. (Kalbotyra, 1986)
The article is devoted to the role of F. Skorina in the formation of the Byelorussian variant of the Church Slavic language. The author points out that the process of the adaptation of the Church Slavic texts to the regional varieties was continued by F. Skorina’s successors – L. Zizany and Smotritsky. F. Skorina only created the codificational norms of the Byelorussian Church Slavic language. L. Zizany and M. Smotritsky reflected the norms in their Grammars.